ASSESSING COLLABORATIVE SKILLS IN A HYBRID PROJECT: A NOVEL FRAMEWORK AND RUBRIC FOR INDONESIAN HIGHER EDUCATION - Lily Kaku; Cinthia Kabua; Eliezo Lang (Journal Neosantara Hybrid Learning, 2025)
The rise of hybrid education in Indonesian higher education has necessitated the development of new assessment approaches to evaluate students’ collaborative skills in digitally mediated learning environments. Traditional group assessment methods often fail to capture the complexity of teamwork processes that occur across both face-to-face and online modalities. This study aims to design, implement, and validate a novel framework and rubric for assessing collaborative competence in hybrid project-based courses. The framework integrates dimensions of digital interaction, task coordination, communication ethics, and reflective collaboration to align with the 21st-century skill requirements in higher education. A design-based research (DBR) methodology was employed, involving three iterative cycles of development, implementation, and evaluation. Participants included 120 undergraduate students from education and engineering faculties at three Indonesian universities. Data were collected through observation, peer-assessment forms, and reflective journals, and analyzed using mixed methods quantitative reliability testing of the rubric and qualitative thematic analysis of students’ reflections. The findings indicate that the new rubric achieved high inter-rater reliability (Cronbach’s ? = 0.89) and effectively differentiated between levels of collaborative performance. Students demonstrated increased awareness of equitable participation and digital communication norms when the rubric was integrated into formative feedback processes. The study concludes that the proposed framework and rubric offer a practical and context-sensitive tool for assessing collaboration in hybrid higher education settings. The model contributes to both pedagogical assessment design and the broader discourse on digital collaboration in Southeast Asian higher education.